Innovation of Local Tax Services to Increase Regional Original Income in Financial Agency and Regional Assets of Sleman Regency - Zakiyah Nugrahaini Ma'wa; Titik Kusmantini; Hendro Widjanarko (Journal of Business Innovation and Research, 2022)
This research is a qualitative research that aims to examine the innovation of local tax services to increase local revenue at the Regional Finance and Assets Agency of Sleman Regency. This research is motivated by the innovation of tax services carried out by Sleman Regency in order to facilitate the community in paying taxes. However, in 2020 the number of realized budgets obtained has decreased. There are 5 people who can be used as respondents in this study, namely: Head of the Regional Finance and Assets Agency of Sleman Regency; Sub Division of Planning, Evaluation & Reporting; General Affairs and Personnel Section; Community users of the e-billing system; and Taxpayer Society. From the results of the interview, it was said that the SOPs that were carried out were in accordance with the rules and mechanisms, but in terms of realization, the taxpayers still often paid past the time limit specified in the SOP. Some of the inhibiting factors for this service innovation are the covid pandemic, lack of awareness of taxpayers, human resources who are still concurrently double jobs so that services to taxpayers are still lacking.